High-Speed Directly Modulated Laser Integrated with SOA - Jia Chen; Dechao Ban; Ya Jin; Jinhua Bai; Keqi Cao; Xinyan Zhang; Hang Yu; Wei Lin; Xiaonan Chen; Ming Li; Ninghua Zhu; Yu Liu (Photonics)
In this paper, we present a directly modulated laser (DML) using a partially corrugated grating (PCG) and integrated with a semiconductor optical amplifier (SOA). The influence of the quasi-high-pass filter properties of the SOA on the bandwidth was explored, resulting in high optical power output at lower current levels, with a bandwidth surpassing 25 GHz and an output power above 25 mW. The PCG design boosts the lasing mode’s resistance to random phase fluctuations at the rear facet, hence boosting the mode stability of the laser with a side-mode suppression ratio (SMSR) of over 44 dB. Furthermore, we performed back-to-back (BTB) 26.5625 Gbps NRZ data transmission experiments at room temperature (25 °C) with a modulation current of 60 mA. The results reveal that the transmitter and dispersion eye closure (TDEC) of the fabricated DML is lower than that of a conventional laser when the SOA area current reaches a specific threshold, demonstrating the enhanced signal transmission capabilities of our design. This laser structure offers a fresh strategy for the development of high-power, high-speed DMLs.